Phagocytes from Mice Lacking the Sts Phosphatases Have an Enhanced Antifungal Response to Candida albicans - David Frank (American Society for Microbiology, 2018)
ABSTRACT Mice lacking expression of the homologous phosphatases Sts-1 and Sts-2 (Sts−/− mice) are resistant to disseminated candidiasis caused by the fungal pathogen Candida albicans. To better understand the immunological mechanisms underlying the enhanced resistance of Sts−/− mice, we examined the kinetics of fungal clearance at early time points. In contrast to the rapid C. albicans growth seen in normal kidneys during the first 24 h postinfection, we observed a reduction in kidney fungal CFU within Sts−/− mice beginning at 12 to 18 h postinfection. This corresponds to the time period when large numbers of innate leukocytes enter the renal environment to counter the infection. Because phagocytes of the innate immune system are important for host protection against pathogenic fungi, we evaluated responses of bone marrow leukocytes. Relative to wild-type cells, Sts−/− marrow monocytes and bone marrow-derived dendritic cells (BMDCs) displayed a heightened ability to inhibit C. albicans growth ex vivo. This correlated with significantly enhanced production of reactive oxygen species (ROS) by Sts−/− BMDCs downstream of Dectin-1, a C-type lectin receptor that plays a critical role in stimulating host responses to fungi. We observed no visible differences in the responses of other antifungal effector pathways, including cytokine production and inflammasome activation, despite enhanced activation of the Syk tyrosine kinase downstream of Dectin-1 in Sts−/− cells. Our results highlight a novel mechanism regulating the immune response to fungal infections. Further understanding of this regulatory pathway could aid the development of therapeutic approaches to enhance protection against invasive candidiasis. IMPORTANCE Systemic candidiasis caused by fungal Candida species is becoming an increasingly serious medical problem for which current treatment is inadequate. Recently, the Sts phosphatases were established as key regulators of the host antifungal immune response. In particular, genetic inactivation of Sts significantly enhanced survival of mice infected intravenously with Candida albicans. The Sts−/− in vivo resistance phenotype is associated with reduced fungal burden and an absence of inflammatory lesions. To understand the underlying mechanisms, we studied phagocyte responses. Here, we demonstrate that Sts−/− phagocytes have heightened responsiveness to C. albicans challenge relative to wild-type cells. Our data indicate the Sts proteins negatively regulate phagocyte activation via regulating selective elements of the Dectin-1–Syk tyrosine kinase signaling axis. These results suggest that phagocytes lacking Sts respond to fungal challenge more effectively and that this enhanced responsiveness partially underlies the profound resistance of Sts−/− mice to systemic fungal challenge.